Anti-inflammatory effect of Rhodiola crenulata extracts through the down-regulation of MyD88 dependent pathway and induction of autophagy. (January 2020) - Lee, Jae-Woong; Kim, Yon-Suk; Dong, Xin; Park, Jin-Su; Shin, Woen-Bin; Kim, Su-Jin; Go, Eun-Ae; Park, Pyo-Jam
Graphical abstract: Highlights: Rhodiola crenulata water extract (RCW) has an anti-inflammatory effect. RCW reduces pro-inflammatory mediators such as NO, IL-6 and IL-1β. RCW regulates MAPK and NF-ĸB signaling of MyD88-dependent pathway. RCW induces HO-1 dependent autophagy expression. Abstract: Rhodiola crenulata ( R. crenulata ) has long been used as a traditional herbal medicine in Eastern Europe and Asia. R. crenulata has been used as an antiacute mountain sickness herbal medicine in Tibet since ancient times and, which is included in the Pharmacopoeia of China. However, although it has been used for a long time in traditional medicine, research on the various effects of R. crenulata is still insufficient. The present study was aimed to investigate anti-inflammatory effect of R. crenulata water extract (RCW) on two macrophages (RAW 264.7 cell and mice peritoneal macrophage cells). We found that RCW inhibit expression levels of iNOS, MAPK, NF-κB proteins and induced autophagy related molecules. Also, RCW reduced inflammatory mediator, NO, IL-6 and IL-1β on both LPS-stimulated macrophage cells. These results suggest that RCW down-regulates inflammation via MyD88 dependent pathway and induces autophagy.